The occupational roles of hospitalized people due to Acquired Immune Deficiency Syndrome - Natália Augusto Nunes Gil; Marysia Mara Rodrigues do Prado De Carlo (O Mundo da Saúde)
Persons hosting Human Immunodeficiency Virus (HIV) and patients having Acquired Immunodeficiency Syndrome (AIDS) suffer from alterations of occupational roles. The aim of this study was to know the configuration of these roles in persons hospitalized as a result of AIDS, in the different stages of the pathology. The casuistry was composed by 40 HIV-positive persons interned, subdivided in three groups considering diagnosis time; the control group was composed by 12 persons, not infected and not interned. Quantitative data were collected by means of the application of the protocol “List of Identification of Occupational Roles”, validated in Brazil, and analyzed by Fisher Exact Test. Interviews were carried out with 20% of the persons of the group of study, for collection of qualitative data, and analyzed according to the content analysis method. We observed that the persons of the group of study presented more losses in occupational roles than those in the control group, and we identified a statistically significant difference for the role of “worker”. We concluded that persons having HIV/AIDS lose occupational roles due to the diseases and hospitalization, something which brings psychosocial and compromises their occupational life.